Whole blood donor behavior and availability after deferral: Consequences of a new ferritin monitoring policy - Spekman, Marloes L.C. (Transfusion, 2020)
BACKGROUND: To prevent (negative consequences of) temporary deferral due to low hemoglobin, the Dutch national blood service Sanquin introduced a ferritin monitoring policy in 2017. Ferritin is measured after the donation (as opposed to before donation for hemoglobin), and low ferritin levels lead to deferral of 6 (ferritin 15‐30 ng/mL) or 12 months (ferritin <15 ng/mL). We explored the consequences of this policy on donor behavior and availability. STUDY DESIGN AND METHODS: We included all Dutch whole blood donors who made a donation (attempt) between 13 November and 31 December 2017. At that point, the ferritin monitoring policy was randomly implemented in 8 of 29 regional clusters of collection centers. We extracted information from Sanquin's donor database about donors' deferrals, subsequent donation attempts, and donation cessation (up to 31 December 2019). Donors deferred for low ferritin were compared to those deferred for low hemoglobin or other reasons, as well as to donors who were not deferred. RESULTS: A total of 55 644 donors were included (11% deferred). For donor behavior, we found that donors deferred for low ferritin less often unsubscribed and switched to other donation types, yet also made fewer donations in the follow‐up period. For availability, we found they were less often deferred, yet they were unavailable to donate for a longer period. CONCLUSION: Results suggest that the implementation of a ferritin monitoring policy may lead to a decrease in donor availability and reduced donations. However, the policy is successful in retaining more donors and reducing low hemoglobin deferrals.